1967
DOI: 10.1172/jci105669
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Immunoglobulin Class, Pattern of Antinuclear Antibody, and Complement-Fixing Antibodies to DNA in Sera from Patients with Systemic Lupus Erythematosus*

Abstract: Abstract. Sera from 55 patients with systemic lupus erythematosus were studied to clarify the significance of the patterns of nuclear fluorescence observed. The sera in which the IgG fraction produced a peripheral pattern of nuclear fluorescence were found to contain complement-fixing antibodies to native DNA and to DNA-histone complexes. This correlation did not exist when complement-fixing activity was compared to the IgM nuclear patterns. Sera which contained only complement-fixing antibodies to denatured D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(51 citation statements)
references
References 35 publications
6
45
0
Order By: Relevance
“…We also demonstrated that IL-4 was required for DN Th cell-induced IgG production from CD1c ϩ B cells, since neutralizing anti-IL-4 mAbs block the production of IgG1 and IgG2. The ability of SLE DN T cells to produce IL-4 and provide help for IgG production is consistent with data showing a critical role for IL-4 in murine models of SLE (42) and the role of IgG autoantibodies in the pathogenesis of lupus nephritis (43). It is striking that the three patients with DN T cells secreting the highest levels of IL-4 were the individuals with the lowest disease activity; each of them had a SLEDAI score of 1.…”
Section: Discussionsupporting
confidence: 88%
“…We also demonstrated that IL-4 was required for DN Th cell-induced IgG production from CD1c ϩ B cells, since neutralizing anti-IL-4 mAbs block the production of IgG1 and IgG2. The ability of SLE DN T cells to produce IL-4 and provide help for IgG production is consistent with data showing a critical role for IL-4 in murine models of SLE (42) and the role of IgG autoantibodies in the pathogenesis of lupus nephritis (43). It is striking that the three patients with DN T cells secreting the highest levels of IL-4 were the individuals with the lowest disease activity; each of them had a SLEDAI score of 1.…”
Section: Discussionsupporting
confidence: 88%
“…The punctate fluorescence of nuclear pore complexes was not apparent on rat liver sections used for routine ANA detection. The autoantibody produced a continuous peripheral (rim) labeling, similar to the fluorescence patterns reported for antibodies to DNA and to lamins (1)(2)(3)(4)(5)(6). However, on cultured cells, the peripheral fluorescence was punctate, and thus, it could not be confused with the continuous labeling associated with these antibodies.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, not all antibodies in the glomeruli of SLE patients are anti-DNA. Some of the characteristics of antibodies to DNA that localize in glomeruli are known; they include high avidity for the antigen (4,37), preferential reactivity with dsDNA (4,8), complementfixing Ig isotypes (2,3,5), and cationic charge, which may be important primarily in the initiation of nephritis (7-1 1,38).…”
Section: Discussionmentioning
confidence: 99%